Optimising biomarkers for accurate ependymoma diagnosis, prognostication and stratification within International Clinical Trials: A BIOMECA study - Rebecca Chapman; David R. Ghasemi; Felipe Andreiuolo; Valentina Zschernack; Arnault Tauziede Espariat; Francesca Romana Buttarelli; Felice Giangaspero; Jacques Grill; Christine Haberler; Simon Paine; Ian C. Scott; Thomas S. Jacques; et al. (2022)
ABSTRACT Background Accurate identification of brain tumour molecular subgroups is increasingly important. We aimed to establish the most accurate and reproducible ependymoma subgroup biomarker detection techniques, across 147 cases from International Society of Pediatric Oncology (SIOP) Ependymoma II trial participants, enrolled in the pan-European “Biomarkers of Ependymoma in Children and Adolescents (BIOMECA)” study. Methods Across six European BIOMECA laboratories we evaluated epigenetic profiling (DNA methylation array); immunohistochemistry (IHC) for nuclear p65-RELA, H3K27me3, and Tenascin-C; copy number analysis via FISH and MLPA (1q, CDKN2A ), and MIP and DNA methylation array (genome-wide copy number evaluation); analysis of ZFTA- and YAP1 -fusions by RT-PCR and sequencing, Nanostring and break-apart FISH. Results DNA Methylation profiling classified 65.3% (n=96/147) of cases as EPN-PFA and 15% (n=22/147) as ST-ZFTA fusion-positive. Immunohistochemical loss of H3K27me3 was a reproducible and accurate surrogate marker for EPN-PFA (sensitivity 99-100% across three centres). IHC for p65-RELA, FISH, and RNA-based analyses effectively identified ZFTA- and YAP1- fused supratentorial ependymomas. Detection of 1q gain using FISH exhibited only 57% inter-centre concordance and low sensitivity and specificity whilst MIP, MLPA and DNA methylation-based approaches demonstrated greater accuracy. Conclusions We confirm, in a prospective trial cohort, that H3K27me3 immunohistochemistry is a robust EPN-PFA biomarker. Tenascin-C should be abandoned as a PFA marker. DNA methylation and MIP arrays are effective tools for copy number analysis of 1q gain, 6q and CDKN2A loss whilst FISH is inadequate. Fusion detection was successful, but rare novel fusions need more extensive technologies. Finally, we propose test sets to guide future diagnostic approaches. Key points We evaluated and cross-validated ependymoma biomarkers in a large prospective clinical trial cohort. Accurate biomarker evaluation is critical to the success of clinical trials and patient care. We propose core and core + biomarker test sets for future molecular stratification. Importance of the Study High-risk paediatric ependymoma has a poor prognosis and is devastating at relapse. Molecularly defined ependymoma types need to be accurately and reliably linked to biomarkers to predict clinical outcomes and design clinical trials. Here, we evaluated and cross-validated ependymoma biomarkers in a large prospective clinical trial cohort highlighting the importance of systematic evaluation of different methods. We provide evidence to guide test selection to support the molecular stratification of paediatric ependymoma and deliver insights into the rationalisation of biomarkers for use in resource-limited settings.